Induced-fit expansion and contraction of a self-assembled nanocube finely responding to neutral and anionic guests - Zhan Yi-Yang; Kojima Tatsuo; Nakamura Takashi; Takahashi Toshihiro; Takahashi Satoshi; Haketa Yohei; Shoji Yoshiaki; Maeda Hiromitsu; Fukushima Takanori; Hiraoka Shuichi (Nature communications, 2018)
Induced-fit or conformational selection is of profound significance in biological regulation. Biological receptors alter their conformation to respond to the shape and electrostatic surfaces of guest molecules. Here we report a water-soluble artificial molecular host that can sensitively respond to the size, shape, and charged state of guest molecules. The molecular host, i.e. nanocube, is an assembled structure consisting of six gear-shaped amphiphiles (GSAs). This nanocube can expand or contract its size upon the encapsulation of neutral and anionic guest molecules with a volume ranging from 74 to 535 Å3 by induced-fit. The responding property of this nanocube, reminiscent of a feature of biological molecules, arises from the fact that the GSAs in the nanocubes are connected to each other only through the hydrophobic effect and very weak intermolecular interactions such as van der Waals and cation-π interactions.UTokyo FOCUS Press releases掲載「取り込む分子の大きさ・形・電荷に応答して膨らんだり縮んだりする分子カプセル」＜研究成果＞ URI: https://www.u-tokyo.ac.jp/focus/ja/press/z0109_00048.html UTokyo FOCUS Press releases "Don't underestimate the Force Researchers discover weak chemical interactions hold together box of infinite possibilities"<Research news> URI: https://www.u-tokyo.ac.jp/focus/en/press/z0508_00014.html